Reducing mommy penalties with daddy quotas. (May 2021) - Dunatchik, Allison; Özcan, Berkay
This paper investigates whether daddy quotas – non-transferable paternity leave policies – mitigate motherhood penalties women face in the labour market. Using the introduction of a daddy quota in Quebec, Canada as a natural experiment, we employ labour force survey data to conduct a difference-in-difference estimation of the policy's impact on a range of mothers' career outcomes, using mothers in the neighbouring province of Ontario as a comparison group. The results suggest Quebec mothers exposed to the policy are 5 percentage points more likely to participate in the labour force and to work full time, 5 percentage points less likely to work part time, and 4 percentage points less likely to be unemployed than they would have been in the absence of the policy. Our results are robust to an alternative semi-parametric difference-in-difference methodology and to a battery of placebo and sensitivity tests. However, we find that the policy's effects are largest 2 to 3 years post-reform, reducing in size and significance thereafter, raising questions about the durability of such effects.